-8b-8(4b-3)=-6(6b+4)

Simple and best practice solution for -8b-8(4b-3)=-6(6b+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8b-8(4b-3)=-6(6b+4) equation:



-8b-8(4b-3)=-6(6b+4)
We move all terms to the left:
-8b-8(4b-3)-(-6(6b+4))=0
We multiply parentheses
-8b-32b-(-6(6b+4))+24=0
We calculate terms in parentheses: -(-6(6b+4)), so:
-6(6b+4)
We multiply parentheses
-36b-24
Back to the equation:
-(-36b-24)
We add all the numbers together, and all the variables
-40b-(-36b-24)+24=0
We get rid of parentheses
-40b+36b+24+24=0
We add all the numbers together, and all the variables
-4b+48=0
We move all terms containing b to the left, all other terms to the right
-4b=-48
b=-48/-4
b=+12

See similar equations:

| 3m/2/5m=2/3 | | 3t+11=8t-9 | | 7x^2+224=-84x | | y=3+60 | | 4(x-4)+8(4x+2)=36 | | y=3+42 | | 8a-22=5a-7 | | y=3+36 | | -4=-4x=12 | | y=3+30 | | 7x^2-5=51 | | -72=6(-3+8x)-3(-8+3x) | | y=21-12 | | 13p+85=2p+96 | | y=21-10 | | (2x–3)+(5x–6)=180 | | 19b+90=15b+98 | | y=21-8 | | (2y–3)+(5y–6)=180 | | 2(2x+4)=-18 | | y=21-6 | | 36=-(n-3)+3(n+7) | | 6a-4=4a+12 | | 5x+610x=31,1 | | 2s+8=4s-70 | | 5-t=0 | | 6(2y-4)=6(2y−4)= | | 6+x+2+40=90 | | x²–2x+12=2x(x+10) | | 7(x-4)+7(-x+8)=28 | | 5v+39=v+43 | | -2x-5(4x+1)=-13 |

Equations solver categories